Agroecology in Slovenia - Vovk Korže, Ana (Revija za geografijo, 2016)
The article presents to agroecology (AE) as a sustainable approach in Slovenia. AE deals with contents as the ecology in agriculture, organic farming, sustainable agriculture, green agriculture, permaculture, ecoremediations, integrated farming and natural agriculture. According to the official definition the term AE means the use of traditional practices that are consistent with the characteristics of the local environment and do not limit only on food production, but also on food processing (recipes), products made from natural materials, especially wood, stone and construction as well as on ways of sustainable relationship to nature (water storage, attitude to water use, attitude to soil, shallow ploughing, attitudes toward animals, plants). We have discovered the concept of AE and its use in Slovenia. In Slovenia the term is limited to the understanding of the importance ecology in agriculture. The representatives of the Slovenian institutions of the Chamber of agriculture and forestry who have a similar project on the topic of AE, designed for agricultural consultants, having described different form of AE. In project Agroecology at the Faculty of Arts we develop educational moduls for teaching AE in practise.
Keywords: agriculture; ecology; ekologija; kmetijstvo; permakultura; remediacija; Slovenia; Slovenija